Dangerous emotions - Lingis, Alphonso, 1933- (University of California Press, 2000)
Alphonso Lingis is an original among American philosophers. An eloquent and insightful commentator on continental philosophers, he is also a phenomenologist who has gone to live in many lands. Dangerous Emotionscontinues the line of inquiry begun inAbuses, taking the reader to Easter Island, Japan, Java, and Brazil as Lingis poses a new range of questions and brings his extraordinary descriptive skills to bear on innocence and the love of crime, the relationships of beauty with lust and of joy with violence and violation. He explores the religion of animals, the force in blessings and in curses. When the sphere of work and reason breaks down, and in catastrophic events we catch sight of cosmic time, our anxiety is mixed with exhilaration and ecstasy. More than acceptance of death, can philosophy understand joy in dying? Haunting and courageous, Lingis's writing has generated intense interest and debate among gender and cultural theorists as well as philosophers, andDangerous Emotionsis certain to introduce his work to an ever broader circle of readers.